HV and MV Distribution Transformers Management in the Electrical Power System - Pana, Leon; Pasculescu, Dragos; Pasculescu, Vlad Mihai; Lazar , Teodora (Research Highlights in Science and Technology Vol. 2, 2023)
Electrical stations (substations) represent basic subsystems of the power grid, being required to establish their modes of operation, evaluation and modelling in order to set a degree of continuity in electric energy supply of load points or consumers. Adoption of optimal solutions of supply in supply with electrical energy of industrial consumers is a very complex problem which involves analyses of a very large number of restrictions and factors, with quasi-determinate and aleatory characteristics. This paper presents a method for determining the optimal apparent power of electric transformers, respective the optimal demand coefficient in the first year of exploitation using the economic criteria and the Matlab –Simulink program.